(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Autobiography is as important a form of literature as the novel. In Marathi it started from the mid19th century. Generally in AD After 1870, the biographies and autobiographies of eminent persons in English began to be translated into Marathi. Autobiographies were written in Marathi based on these translated writings.